Sheet C1 Pattern Number Recognition Using Artificial Immune System Optimization - Yuniarti Denita, Sari; Tri Basuki, Kurniawan; Edi Surya, Negara; Tata, Sutabri (INTI International University, 2022)
When the general election is held in Indonesia, Sheet C1 serves as a record of the results of vote counting at each polling location (TPS). Human error makes it difficult to enter accurate vote data during the recapitulation phase, where the number of votes is a crucial piece of information for the conduct of general elections. The problem was that the KPPS (Voting Committee Group) failed to clearly write the legitimate vote acquisition for each TPS on sheet C1, which caused difficulty for the KPU employees when entering the data. In order to recognize the numerical patterns on sheet C1, we, therefore, require a method that uses the Artificial Immune System (AIS), specifically the CSA (Clonal Selection Algorithm) algorithm, which is one of the AIS system's algorithms for optimization. The CSA method will be used in this research to accomplish number pattern recognition and to examine the operation of number pattern character recognition.